Penerapan Strategi Content Marketing Untuk Membangun Brand Awareness Produk Skincare Skintific - Erwin Permana; Nadya Amanda; Noer Fhadya Dwi Aninda; Syamsurizal (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
Analysis of digital marketing in increasing brand awareness has been carried out very often. However, there has not been much analysis that specifically carries out marketing content analysis to increase brand awareness. This research aims to conduct content marketing analysis to increase brand awareness of skincare products. The research was conducted using a qualitative descriptive approach. Research data comes from the results of reviews of official publications and data searches in various digital databases. The research results show that there are several main content marketing strategies carried out by brands by paying attention to several factors, namely collaborating with influencer marketing through creative marketing campaigns, providing attractive discounts and promotions on certain dates in the form of flash sales, and giveaways to get audience engagement which ultimately resulting in increased sales. This is related to design factors, current events, reading experience, time and also the tone of the content marketing strategy carried out by skintific. Apart from that, Skintific also provides platforms on various social media as a reference source of information and increases marketing sales in various marketplaces such as Shopee, TikTok and Lazada. In this research, general strategies are explained so that for further research it is recommended to be more specific, for example a strategy by utilizing influencer marketing to produce a deeper understanding and be easier to understand